DEVELOPMENT OF MORAL VALUE POETRY WRITING THROUGH PROJECT-BASED LEARNING - Reni Oktaviani; Siti Ansoriyah; Muhammad Fajar Rizkia; Sam Mukhtar Chan (Universitas PGRI Palembang, 2025)
The learning process demands proficiency in core language skills listening, reading, speaking, and writing. Among these, writing is essential and must align with current Enhanced Spelling Guidelines (Ejaan yang Disempurnakan) to prevent miscommunication. However, students often face challenges in writing, especially beginners, due to a lack of interest in reading and the complexity of textbook language, which hinders idea development. Accessible and engaging reading materials are crucial to foster student interest and creativity. Misconceptions that adherence to proper spelling rules is unnecessary are particularly problematic for students in the Indonesian Language and Literature Education program, where accurate and appropriate writing is fundamental, including in fiction. Writing proficiency plays a vital role in courses such as Popular Writing Skills. This study aims to enhance students’ ability to write morally themed poetry through project-based learning. Employing a Research and Development approach with the ADDIE model, data were gathered via observation, questionnaires, and students’ poetry writing outcomes, and analyzed using expert and peer assessments. The findings indicate that project-based learning significantly improves the poetry writing skills of first-year students, positively influencing their writing quality and engagement, particularly in integrating moral values into their creative work.